Collimation of diverged beam using a cylindrical lens in a silicon‐based end‐fire optical phased array. Issue 7 (1st March 2020) - Yoon, H.; Kim, Y.; Shim, J.‐S.; Park, H.‐H.
Abstract : The authors demonstrate the collimation of a vertically diverged beam emitted from a silicon‐based end‐fire optical phased array (OPA) using an aspheric cylindrical lens. A micro‐cylindrical lens with a numerical aperture of 0.8 was placed near the focal length in front of an 1 × 16 end‐fire OPA with a half‐wavelength (775 nm) radiator array pitch for a 1550 nm wavelength. The lens provided a great collimation effect, reducing the vertical divergence angle from 95.6° to 6.7° during horizontal beam steering over ±30°. The horizontal divergence angle showed some expansion, from 7.6° to 10°, due to the angle‐dependant curvature of the lens and the distance to the lens surface.